A Mobile Vocabulary Learning App for Engineering Contexts: Gamification, Self-Directed Learning, and User Progress Tracking - Anita Nursi; Resmi Darni; Dony Novaliendry (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
Engineering students frequently face challenges in mastering technical English vocabulary due to its context-dependent and specialized nature. To address this issue, this study developed a mobile application that facilitates self-directed learning of domain-specific vocabulary through gamified activities. The application was designed using the Flutter framework and integrated with Firebase for real-time data management and user tracking. It features two interactive games—Word Guess and Word Match—as well as text-to-speech functionality, a limited hint system, and visual progress tracking through mastery counts and progress bars. Vocabulary items are organized into three thematic categories: General Terms, Tools, and Instructions, each structured through JSON-based data management for scalability and ease of maintenance. Empirical evaluations involving expert review yielded a high validity score (M = 4.6/5), confirming the application’s pedagogical soundness and technical stability. The integration of gamification and progress visualization significantly enhanced learner motivation, autonomy, and engagement. This study contributes a replicable model for combining Flutter–Firebase development with instructional design principles to advance technology-enhanced language learning in engineering education.